FAMILY DYNAMICS, FAMILY BREAKUPS, AND THEIR IMPACTS ON CHILDREN - Yayah Khisbiyah (Buletin Psikologi, 1994)
The number of family breakups has been increasing in the last few decade, particularly in the developed, industrial world. By far the highest divorce rate in the industrial countries is that of the United States. According to current rates, about half of all American marriages are dissolved.